Potencial genético de populações segregantes de feijoeiro-comum para escurecimento e cocção dos grãos - Silva, Fernanda de Cássia (2012)
The obtain cultivars which have slow darkening allows storage of grains for a longer period, making it more flexible bean market. Recent studies have demonstrated the possibility of selecting line of common bean grain slow darkening. The objectives of this study were i) to select parents who meet slow darkening, low cooking time after storage and productivity, ii) select promising populations segregating for extraction of lines, iii) determine the relationship between the slow darkening of the grains and shortest time cooking after storage, and iv) determine the genetic control of slow darkening the grains in the populations evaluated. We used twelve common bean genotypes divided into two groups: group I consists of two genotypes with slow darkening of grains, and group II consisted of ten genotypes with regular darkening of grains, which were crossed according to the partial diallel genetic design, yielding twenty populations. The population obtained in this diallel were evaluated, along with his parents in Santo Antônio de Goiás/inverno/2010-F3 (STO) and Ponta Grossa/águas/2010-F4 (PGA) in randomized complete block design with three replications and four lines meters. The characters were: the darkening of grain during the storage, by grading scale, the cooking time after storage (TCA) by means of Mattson cooker, and yield. We conducted analyzes of individual variance and joint, and then analyzes diallel during storage. It was observed phenotypic segregation to grain in the darkness of populations, from the chi-square test. For the darkening of grains, the parents BRSMG Madrepérola (group I), IPR Siriri e CNFC 10429 (group II) contributing to the slow darkening of the grain, with high CGC. The population that better were BRSMG Madrepérola x CNFC 10429 and BRSMG Madrepérola x IPR Siriri. For TCA, the parents who contributed to low cooking time were BRS Requinte (group I), IPR Saracura and BRSMG Majestoso (both group II). The populations that showed the reduction to this character were BRS Requinte x BRS Estilo and BRS Requinte x BRS 9435 Cometa. For grain yield the parents who contributed to this character additions were BRSMG Madrepérola (group I), BRS Estilo and CNFC 10429 (group II). Among the best populations for productivity, the most relevant populations BRSMG Madrepérola x CNFC 10429, BRSMG Madrepérola x CNFC10429, BRSMG Madrepérola x BRS Estilo, BRS Requinte x CNFC 10429. There were no parents and populations who meet the desirable phenotypes for the tree characters together. However, the line CNFC 10429 and populations BRSMG Madrepérola x CNFC 10429 e BRSMG Madrepérola x BRS Estilo sood out by gathering slow darkening and productivity, with promising for plant breeding. No linear association has been detected between the slow darkening and shorter cooking grain after storage. High correlation was found between the evaluation periods for the darkening of the grain. For the darkening of the grain populations were detected with mono and bigenic inheritance, indicating that this character is controlled by few genes. It was found also that for the elucidation of the genetic control of slow darkening of grain these is a need to evaluate different populations in different environments due to the presence of G x E interation for this trait. Based on these results suggest that there is variability in the darkening of the grains and parents are well variability in the darkening of the grains and parents are well adapted, and these may lead to promising populations, aiming at the selection of strains with slow darkening of the grains.